The Preeclampsia intervention with Esomeprazole (PIE) trial: A double blind, randomised, placebo-controlled trial to treat early onset severe preeclampsia - Cluver, Catherine Anne (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.